Morphological characterisation of the Tswana goat - Katongole, J.B.D.; Sebolai, B.; Madimabe, M.J. (International Livestock Research Institute, 1996)
A survey study was conducted in two districts of Botswana to obtain data on the morphological characteristics of Tswana goats. There were five different locations chosen, namely Oodi, Artesia and Mochudu in the Kgatleng District and Kopong and Thamag in Kweneng district. In each location, 16 to 20 farmers with goats were randomly selected and records: taken on a random sample of 10 goats from each farmer. The different body dimensions that were measured, included heart girth (HG), diagonal body length (BL), height at withers (HW), body weight (BW) and rump height (RH). Records were also taken on presence of horns (HO), wattles (Wa) and beards (Bd), coat colours (white, black, black and white, brown, brown and white) and hair structure (short coarse, long coarse, short smooth and long smooth). The results showed age-dependent sexual differences in the body dimensions that were measured. The apparent wide variation in coat colours and hair structure among Tswana goats observed in this study is indicative of the fact that the breed has not yet been purified through selection breeding and therefore great opportunities exist for its improvement. The propensity toward white coat colour and/or in combination with others, especlally black and brown, appears to be an adaptive, charactenstic of Tswana goats to withstand pronounced seasonal fluctuations in the intensity and duration of light, heat and cold. Finally the Tswana goat can be classified as a multicoloured, medium size breed with long lopping ears, short coarse hair tructure, predominantly bearded and horned.